2015
DOI: 10.1177/1557988315606962
|View full text |Cite
|
Sign up to set email alerts
|

Young Black Gay/Bisexual and Other Men Who Have Sex With Men: A Review and Content Analysis of Health-Focused Research Between 1988 and 2013

Abstract: Black young gay, bisexual, and other men who have sex with men (YGBMSM) are at high risk for negative health outcomes, though this population is underrepresented in the health literature. An extensive literature review and content analysis of health-related peer-reviewed articles was conducted that targeted Black YGBMSM, examining five content areas: sexual health, health care, substance use, psychosocial functioning, and sociostructural factors. A coding sheet was created to collect information on all conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 127 publications
1
28
1
Order By: Relevance
“…Much of the research exploring sexual development of adolescents has focused on adolescents who identify as heterosexual (Fortenberry et al, 2010). Prior work exploring the sexual identity development experiences of sexual minority adolescents has failed to understand the sexual development of youth who may exist at the intersection of multiple marginalized identities, such as Black and bisexual (Dubé & Savin-Williams, 1999; Jamil, Harper,& Fernandez, 2009; Rosario, Schrimshaw,& Hunter, 2004,2008; Rosario, Schrimshaw, Hunter,& Braun, 2006; Toomey, Huynh, Jones, Lee, & Revels-Macalinao, 2017; Wade & Harper, 2015). Past work suggests that bisexual youth of color, including Black bisexual male adolescents (BBMA), may have significant and unmet sexual and reproductive as well as mental health needs during sexual development (Chun & Singh, 2010; Dodge et al, 2016; Friedman et al, 2014; Saewyc et al, 2009), which are unique and distinct from those adolescents who identify as gay, lesbian or heterosexual (Friedman et al, 2014; Mereish, Katz-Wise, & Woulfe, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the research exploring sexual development of adolescents has focused on adolescents who identify as heterosexual (Fortenberry et al, 2010). Prior work exploring the sexual identity development experiences of sexual minority adolescents has failed to understand the sexual development of youth who may exist at the intersection of multiple marginalized identities, such as Black and bisexual (Dubé & Savin-Williams, 1999; Jamil, Harper,& Fernandez, 2009; Rosario, Schrimshaw,& Hunter, 2004,2008; Rosario, Schrimshaw, Hunter,& Braun, 2006; Toomey, Huynh, Jones, Lee, & Revels-Macalinao, 2017; Wade & Harper, 2015). Past work suggests that bisexual youth of color, including Black bisexual male adolescents (BBMA), may have significant and unmet sexual and reproductive as well as mental health needs during sexual development (Chun & Singh, 2010; Dodge et al, 2016; Friedman et al, 2014; Saewyc et al, 2009), which are unique and distinct from those adolescents who identify as gay, lesbian or heterosexual (Friedman et al, 2014; Mereish, Katz-Wise, & Woulfe, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Prior work focused on the sexual behavior of BBMA overwhelmingly focuses on the sexual risk experiences of these young men (Kipke et al, 2007;Mustanski, Newcomb, Du Bois, Garcia, & Grov, 2011;Wade & Harper, 2015;Young& Meyer, 2005). However, these studies have not elucidated how normative adolescent sexual development and behavior might impact those risks.…”
Section: Introductionmentioning
confidence: 99%
“…Though Black gay/bisexual male adolescents and emerging adults are one of the groups most affected by HIV in the U.S., few behaviorally-focused prevention interventions have been created specifically for this population (Harper & Riplinger, 2013). Much research has shown the detrimental health effects of various types of oppression (e.g., racism, heterosexism, HIV stigma) that pervade the lives of these young men within the U.S. (Arnold, Rebchook & Kegeles, 2014; Bogart, Wagner, Galvan et al, 2011; Bogart, Landrine, Galvan, et al, 2013; Wade & Harper, 2017). As such, we document the utility of using empowerment as a framework for understanding how oppression impacts the health and wellbeing of Black gay/bisexual male youth, and offer critical consciousness as an effective method of operationalizing empowerment in behavioral interventions for this population.…”
mentioning
confidence: 99%
“…While cultural messages appear to impact participation in risk behaviors among young Black heterosexual men, there is a paucity of research on their Black gay and bisexual counterparts (Wade & Harper, ). Frequently, Black gay and bisexual young men must not only contend with the negative societal reactions to their sexual orientation but also may experience racial prejudice, limited economic opportunities and resources, and limited acceptance within their own families and cultural communities (Harper & Wilson, ; Quinn, Dickson‐Gomez & Kelly, ; Thoma & Huebner, ).…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative research methods provide an opportunity to gain a nuanced and rich understanding of the identification and interpretation of cultural messages as voiced by members of this community. Despite its multiple benefits as a method of inquiry, there has been a noteworthy deficit of qualitative studies conducted with Black gay and bisexual young men (Wade & Harper, ).…”
Section: Introductionmentioning
confidence: 99%